Maintaining feed supply in dry areas - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
Use of Acacia pods as feed, growing forage crops, feed and water for pregnant goats, and checking for mineral deficiencies.